Pengaruh Overconfidence Dimoderasi Usia Terhadap Keputusan Investasi pada Pengguna Aplikasi Bibit - Leonny Jessica Prameswari; Tiar Lina Situngkir (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research was conducted to test the effect overconfidence on investment decisions among investors in the Bibit application and examine whether the age variable can moderate this relationship. The method used in the research is a survey. There are independent variables studied, namely overconfidence, while the dependent variable measured is investment decisions. The sample used was Bibit application users who were active in investment activities, totaling 368 respondents. Verification analysis was carried out using Simple Linear Regression Analysis to test the effect overconfidence on investment decisions. To test the influence of the moderating variable age on the relationship between overconfidence and investment decisions, testing was used Moderation Analysis by using syntax macro Process 4.2 developed by Andrew F. Hayes. The research results show that overconfidence influence investment decisions among Bibit application users. Investors in the Bibit application tend to be bolder in making investment decisions because they have high self-confidence. In addition, age was shown to moderate the relationship between overconfidence and investment decisions, where younger investors tend to be more confident in choosing investments, often without taking risk into account properly, due to lack of experience. Based on these findings, it is recommended to provide more complete and educational information, so that users can make more rational and informed investment decisions.